Rebels All! : Rebels All! A Short History of the Conservative Mind in Postwar America - Mattson, Kevin, 1966- (Book collections on Project MUSE., 2008)
Do you ever wonder why conservative pundits drop the word "faggot" or talk about killing and then Christianizing Muslims abroad? Do you wonder why the right's spokespeople seem so confrontational, rude, and over-the-top recently? Does it seem strange that conservative books have such apocalyptic titles? Do you marvel at why conservative writers trumpeted the "rebel" qualities of George W. Bush just a few years back? There is no doubt that the style of the political right